Advances and challenges in mechanical support for cardiogenic shock complicating acute myocardial infarct: a comprehensive review of the latest data - Papanikolaou, Amalia; Chlorogiannis, David Dimitris; Apostolos, Anastasios; Mavridis, Theodoros; Tsigkas, Grigorios (Frontiers in Disaster and Emergency Medicine, 2024)
Cardiogenic Shock represents a life-threatening condition characterized by high mortality and a spectrum of clinical presentations, complicating 5%−10% of patients presenting with Acute Coronary Syndromes. Despite advances in interventional cardiology and emergency medicine, mortality rates remain extremely high and evidence concerning its management is scarce. Consequently, the decision making relies heavily on a single operator's experience. This comprehensive review aims to provide a thorough update on the latest proof regarding mechanical circulatory support devices of the left ventricle and examines the role of the classification scores on the selection of the appropriate patient and timing for the initiation of the device. The five necessary steps to a successful mechanical circulatory support device's insertion. The picture was made by Pixlr AI Image Generator.